Solar technologies for electricity production: An updated review. (1st September 2021) - Aqachmar, Zineb; Ben Sassi, Hicham; Lahrech, Khadija; Barhdadi, Abdelfettah
Abstract: This review details the most recent advancement in solar electricity production devices, in order to offer a reference for the decision-makers in the field of solar plant installation worldwide. These technologies can be classified into three main categories, namely Photovoltaics, Thermal, and Hybrid (thermal/photovoltaic). Hence, this paper begins by laying out the methodology that is used for conducting this research. Next, solar electricity production technologies are investigated and their sub-classifications are detailed to determine their resource requirements and characteristics. Subsequently, a thorough discussion is carried out. Followed by an assessment of the environmental and financial performances of each technology. Moreover, a statistical study is undertaken to highlight the efficiency and performances of each solar technology, as well as to determine their rankings in terms of electricity production worldwide. Finally, research trends related to the development of solar electricity plants are provided. Highlights: Provides thorough investigation of the solar PV, CSP and hybrid technologies. Recent advances in hybrid solar power technologies are analyzed. GIS based maps and summary of the installed solar power plants worldwide are given. Updated economic and environmental analyses of solar technologies is carried out. Presents future research trends in solar technologies.